Usage of Mobile X-Rays in Active Case-Finding for Tuberculosis - Cindra Paskaria; Elizabeth Wianto; Hapnes Toba (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2024)
Indonesia has the world’s second-highest number of tuberculosis cases. More than 300,000 cases of tuberculosis in Indonesia have not been diagnosed or recorded, which are known as the missing cases. Undiagnosed tuberculosis patients will cause the spread of tuberculosis bacteria to other people. Active case-finding of tuberculosis needs to be carried out to find more cases of tuberculosis in the community. Purwakarta is one of the districts with the highest incidence of tuberculosis in West Java province. Maranatha Christian University, in collaboration with the Purwakarta District Health Office, carried out active case-finding activities in the Plered subdistrict, which is the subdistrict with the highest tuberculosis cases in the Purwakarta district. Active case-finding activities were carried out at the ‘balai desa’ (village hall). The flow of active case-finding activities consists of registration, anamnesis, physical examination, sputum sampling, and chest x-ray examination using a mobile x-ray. Active case-finding activities in the Plered subistrict were attended by 364 patients. Chest x-ray examination was carried out on 231 patients, and 21 of them were diagnosed with tuberculosis. Active case-finding tuberculosis using a combination of; anamnesis, physical examination, sputum examination, and x-rays, can be applied to facilitate public access to health services and increase the rate of finding tuberculosis cases.